Urban Ecosophy for a Post-Colonial Ecohumanism of the City - Sellier, Dominique (Journal of Ecohumanism, 2022)
Ecosophy traces its etymological roots to the ancient Greek wisdom (sophia) of the household (oÃ¯kos), and can be understood as a form of ethics to inhabit the earth. Reflecting on the current challenges of the city, like the relation to the nature, or the social and ethnic inequalities in the urban space and through the ecosophical gaze of Arne NÃ¦ss and Felix Guattari allows us to address core issues of an urban ecosophy.Â  Within NÃ¦ss ecosophy of the â€œself-realizationâ€, the paper is pointing the link with his ontology of the relation with GandhiÂ´s insight on non-violence and the importance of the â€œsense of placeâ€ with the understanding and identification to the local environment. GuattariÂ´s ecosophy as the paper will show, leads also to the concepts of relation and of the â€œTout-mondeâ€ from the post-colonial thinker, and friend of him, Edouard Glissant. Furthermore, StieglerÂ´s concept of neguanthropocene and considering cities as â€œcomplex exorganismsâ€ echoes GuattariÂ´s urban ecosophy with the emergence of the â€œdata cityâ€ performing a new kind of colonialism with data in the urban space. Finally, the essay will demonstrate how the urban ecosophy, as a practical ecosophy, in correspondence with ecohumanism, is proposing a decentring of humanism by considering the ecology in the city.Â  It makes then possible to reconcile a modernist philosophy of individual and collective emancipation and deployment of subjectivities in the city, the idea of universalism with a world citizenship, with an emerging philosophy of respect and ethic for the living.